The Impact of Business and Financial Literacy Training for Young Entrepreneurs in Bosnia-Herzogovina - Bruhn, Miriam; Zia, Bilal (World Bank, Washington, DC, 2012)
Firms in developing countries are widely known to face many constraints, from lack of access to finance and physical capital to poor infrastructure. The course seems to have been particularly effective at promoting business growth for those entrepreneurs who exhibited higher levels of financial literacy at the baseline. Policymakers might therefore consider targeting business training resources towards existing firms, with an emphasis on particularly teachable behaviors.